Pengaruh intellectual capital terhadap profitabilitas dengan pertumbuhan perusahaan sebagai variabel moderasi - Erika Angelika; Alfinur; Ati Retna Sari (Fakultas Ekonomika dan Bisnis Universitas PGRI Kanjuruhan Malang, 2020)
This study aims to examine and explain the effect of Intellectual Capital on Profitability with Company Growth as a Moderation Variable in Food and Beverage Companies Listed on the Indonesia Stock Exchange in 2016-2018 and analyzed using moderated regression analysis, and using the t test. The number of samples is 13 companies, and the sampling method used is purposive sampling. This research variable consists of Value Added Human Capital, Structural Capital Value Added and Value Added Capital Employed as an independent variable, profitability as the dependent variable, and company growth as a moderating variable. The analysis showed that partially VAHU, STVA and sales growth had a significant effect on profitability, and VACA had no significant effect on profitability. Company growth strengthens the influence of VAHU on profitability and company growth strengthens the effect of STVA profitability, while company growth does not moderate the effect of VACA on profitability.